Pengurusan Pemuliharaan Instrumen Beduk Dalam Budaya Masyarakat Melayu Di Sungai Besar, Selangor - Muhamad Syahmi, Bin Dorahman (Universiti Malaysia Sarawak (UNIMAS), 2018)
In this study, the researcher will examine the issue of the lack of use of beduk instruments in Malaysia. The researcher emphasized the management, conservation and promotion of Masjid Badli Shah, Parit 6. Therefore, the researcher used the field work method through interview with five selected informants to obtain analytical data. The researcher will examine the factors that influence the lack of use of the bedrock on the Malay community. The findings show that the use of beduk is only releven in the village area with the aim of calling the community to congregate.